Process-oriented Information Logistics: Aligning Enterprise Information with Business Processes - Michelberger, B.; Mutschler, B.; Reichert, M. (2012 IEEE 16th International Enterprise Distributed Object Computing Conference, 2012)
Today, enterprises are confronted with a continuously increasing amount of data. Examples of such data include office files, e-mails, process descriptions, and data from process-aware information systems. This data overload makes it difficult for knowledge-workers to identify the information they need to perform their tasks in the best possible way. Particularly challenging is the alignment of process-related information with business processes. In fact, process-related information and business processes are usually managed separately. On the one hand, enterprise content management systems, shared drives, and Intranet portals are used for organizing information, on the other hand, process management technology is used to design and enact business processes. With process-oriented information logistics (POIL) this paper presents an approach for bridging this gap. POIL enables the process-oriented and context-aware delivery of process-related information to knowledge-workers. We also present a clinical use case and a proof-of-concept prototype to demonstrate the application and benefits of POIL.